2018
DOI: 10.1186/s12888-018-1803-y
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and burden of illness in adults with newly diagnosed attention-deficit/hyperactivity disorder in Sweden

Abstract: BackgroundThis observational, cross-sectional, retrospective chart review aimed to identify factors determining health-related quality of life (HRQoL) in adults with newly diagnosed attention-deficit/hyperactivity disorder (ADHD) in Sweden.MethodsAdult participants with a new clinical diagnosis of ADHD were enrolled from two specialist outpatient clinics in Stockholm, Sweden, from 2013 to 2015. Data extracted from patient records included demographics, clinical characteristics and comorbid psychiatric diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
(37 reference statements)
2
18
0
1
Order By: Relevance
“…In line with previous research, we found no differences in ADHD diagnosis between men and women (Agnew-Blais et al, 2016;Moffitt et al, 2015). A recent report by Ahnemark et al (2018) on a Swedish adult population with a recent diagnosis of ADHD, indicated that 57% of the sample was female. Our finding sheds light on the fact that regardless of gender, people have the same risk of developing ADHD.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous research, we found no differences in ADHD diagnosis between men and women (Agnew-Blais et al, 2016;Moffitt et al, 2015). A recent report by Ahnemark et al (2018) on a Swedish adult population with a recent diagnosis of ADHD, indicated that 57% of the sample was female. Our finding sheds light on the fact that regardless of gender, people have the same risk of developing ADHD.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the implications on life and the complexity of unifying the criteria to select assessments on people with ADHD, several authors have argued that health-related quality of life (HRQoL) is the most suitable indicator for analyzing the impact of this disorder on daily life and well-being [9,[13][14][15][16]. HRQoL has been defined as a multidimensional construction that comprises several domains related to health and well-being, as it also refers to the subjective and objective impact of dysfunction associated with a disease or injury, medical treatment, and health status [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has also proposed that an adult-onset form of ADHD may exist in some populations 5,6 . ADHD can have a significant negative impact on professional, financial, social and emotional aspects of adult life 7,8 and our first report of this study published elsewhere 9 adds to the limited published information related to the burden of ADHD in a population of adults (Swedish) with newly diagnosed ADHD.…”
Section: Background and Study Overviewmentioning
confidence: 71%
“…The adjusted mean EQ-5D total score was 0.08 points lower in females than males, although the difference only just reached statistical significance (p = 0.049) 9 . According to a 2001 report, the mean EQ-5D total score is also lower in females than in males in the general Swedish population (by 0.03 points, p < 0.001) 10 , a difference which may have been reflected in our study.…”
Section: Female Gender Predicted Poor Hrqolmentioning
confidence: 82%
See 1 more Smart Citation